Mehdi Golshani's Philosophy on the Position of Science in Islam - Darisman, Dede (Research and Development Institution, Darussalam Institute for Islamic Studies, 2020)
This article seeks to explore Mehdi Golshani's thoughts on the position of science in religion. By using the literature study method, this study finds that Mehdi Golshani's idea of Islamic science is a form of epistemological effort to intervene in responding to the debate around the relationship between science and religion. According to him, science is not merely a collection of theories, concepts, and natural laws, but is also part of the metaphysical reality in which divine values are stored. Descriptive analysis of Mehdi Golshani's view of Islamic science provides an understanding that science cannot be reduced to the physical realm (material) but must be combined with the supernatural realm (religion) so that it becomes an inseparable whole.